Analysis of Copyright Implementation and Challenges in Photography in the Digital Era in Indonesia - Mochamad Habiibi; Dr. R. Rahaditya, SH.,MH (Dinasti Research, 2025)
The enforcement of copyright law against photography infringements in Indonesia faces several challenges in the digital age. Although Law Number 28 of 2014 on Copyright provides clear legal protection for photographic works, effective law enforcement is often hindered by the lack of legal awareness among the public, limited surveillance of works spread across the internet, and the use of new technologies that facilitate copyright violations. This study aims to examine the effectiveness of law enforcement against copyright infringements on photography in Indonesia and identify the key challenges faced by photographers in protecting their copyrights in the digital era. Strategic steps involving the government, law enforcement agencies, and the private sector are needed to raise legal awareness and strengthen the law enforcement system in addressing the increasingly complex photography copyright violations.